Building a pediatric rare lung disease program: It takes a community of villages. Issue 11 (17th August 2022) - Vece, Timothy J.; Gower, William A.; Davis, Stephanie D.; Austin, Ashley; McKinzie, Cameron J.; Hatch, Joseph E.; Davis, Miriam; Hagood, James S.
Abstract: Pediatric rare lung disease programs are increasing in number due to an increase in recognition of the diseases, increased clinical and research interest in children's interstitial lung disease, and the expansion of the children's interstitial lung disease research network. Due to this increased interest newly graduated trainees in pediatric pulmonology and other physicians are often starting new programs, which can be daunting. We provide some guidance for new programs based on our experiences.